Effectiveness of COVID-19 XBB.1.5 monovalent mRNA vaccine in Korea: interim analysis - Nham, Eliel; Sohn, Jang Wook; Choi, Won Suk; Wie, Seong-Heon; Lee, Jacob; Lee, Jin-Soo; Jeong, Hye Won; Eom, Joong Sik; Choi, Yu Jung; Seong, Hye; Yoon, Jin Gu; Noh, Ji Yun; et al. (Frontiers in Immunology, 2024)
As coronavirus disease-2019 (COVID-19) becomes an endemic disease, the virus continues to evolve and become immunologically distinct from previous strains. Immune imprinting has raised concerns about bivalent mRNA vaccines containing both ancestral virus and Omicron variant. To increase efficacy against the predominant strains as of the second half of 2023, the updated vaccine formulation contained only the mRNA of XBB.1.5 sublineage. We conducted a multicenter, test-negative, case-control study to estimate XBB.1.5 monovalent vaccine effectiveness (VE) and present the results of an interim analysis with data collected in November 2023. Patients who underwent COVID-19 testing at eight university hospitals were included and matched based on age (19-49, 50-64, and ≥65 years) and sex in a 1:1 ratio. VE was calculated using the adjusted odds ratio derived from multivariable logistic regression. Of the 992 patients included, 49 (5.3%) received the XBB.1.5 monovalent vaccine at least 7 days before COVID-19 testing. Patients with COVID-19 (cases) were less likely to have received the XBB.1.5 monovalent vaccine (case 3.5% vs. control 7.2%, p=0.019) and to have a history of COVID-19 within 6 months (2.2% vs. 4.6%, p=0.068). In contrast, patients with COVID-19 were more likely to be healthcare workers (8.2% vs. 3.0%, p=0.001) and to have chronic neurological diseases (16.7% vs. 11.9%, p=0.048). The adjusted VE of the XBB.1.5 monovalent mRNA vaccine was 56.8% (95% confidence interval: 18.7-77.9%). XBB.1.5 monovalent mRNA vaccine provided significant protection against COVID-19 in the first one to two months after vaccination.